Transcatheter aortic valve implantation for severe, non‐calcified aortic regurgitation and narrow aortic root: Description from a case report of a new approach to potentially avoid coronary artery obstruction. Issue 2 (14th November 2012) - Dumonteil, Nicolas; Marcheix, Bertrand; Lairez, Olivier; Laborde, Jean‐Claude
<x xml:space="preserve">Abstract</x> Transcatheter aortic valve implantation is a possible, although off‐label, alternative to conventional aortic valve replacement for high‐surgical‐risk patients with severe, non‐calcified aortic regurgitation (AR). To date, feasibility has only been demonstrated with the Medtronic CoreValve prosthesis (MCV). This prosthesis needs the aortic sinuses to have enough width to avoid coronary obstruction. We report a case of MCV implantation for severe AR where the narrow aortic root theoretically precluded the technique. Good procedural outcome was achieved thanks to a strategy of implantation with planned positioning of the prosthesis leaflets away from the coronary arteries. © 2013 Wiley Periodicals, Inc.